FAKTOR-FAKTOR KEUANGAN YANG MEMPENGARUHI RATING SUKUK DENGAN MENGGUNAKAN MODEL REGRESI MULTINOMIAL LOGISTIK - Devi Arum Saputri; Noven Suprayogi (Universitas Airlangga, 2018)
This research aims to explain the influence of financial performance towards therate of sukuk listed in Indonesia Stock Exchange in the period of 2013 to 2015. Independent variables used is the ratio of return on assets, current ratio and growth as a proxy for financial performance, and the dependent variable used is sukuk rating. The analytical method used in this study is Multinomial Logistic Regression.The results of this study showed that simultaneous financial performance significantly affect the rating sukuk, and individually there are two models produced.In the first model, the ROA and CR have positive influence on the idA rating compared to the idAAA rating. In the second model, the ROA and CR also have positive influence on the idAA rating compared to the idAAA rating. REFERENCESAfiani, Damalia. 2013. Pengaruh Likuiditas, Produktifitas, Profitabilitas dan Leverage terhadap Peringkat Sukuk. Accounting Analysis Journal, Vol.2 (01).Arundina, Tika, et al. 2015. The Predictive Accuracy of Sukuk Ratings; Multinomial Logistic and Neural Network Inferences. Jurnal Keuangan, 34.Asbaugh, Holis, et al. 2004. Corporate Governance and the Cost of Equity Capital.Madison.Askari, Hossein, et al. 2009. New Issues In Islamic Finance and Economics “Progress and Challenges”. Asia:John Wiley and Sons (Asia) Pte.ltd.Brealey, Myres, dan Marcus. 2008. Dasar-dasar Manajemen Keuangan Perusahaan. Jilid 1. Penerbit Erlangga. Jakarta.Brigham, Eugene F. And Houston F. Joel. 2009. “Fundamentals of Financial Management” Dasar-dasar Manajemen Keuangan. Edisi 10. Salemba Empat. Jakarta.Bursa Efek Indonesia. 2016. Data Perusahaan Tercatat. (Sumber: http://www.idx.co.id, diakses pada tanggal 30 Agustus 2016).Burton, Bruce. 2000. The Determinants of Credit Rating in the United Kingdom Insurance Industry. School of Fnance and Law Working Paper Series no 19.Djalal, Nachrowi, et al. 2006. Pendekatan Populer dan Praktis Ekonemetrika untuk Analisis Ekonomi dan Keuangan. Jakarta.Duwi, Priyanto. 2009. 5 Jam Belajar Olah Data dengan SPSS 17. Penerbit Andi. Yogyakarta.Fatwa Dewan Syari'ah Nasional No: 32/DSN-MUI/XI/2012 Tentang Surat Berharga Jangka Panjang berdasarkan Prinsip Syariah.Ghozali, Imam. 2005. Aplikasi Analisis Multivariate dengan Program SPSS, Badan Penerbit Universitas Diponegoro, Semarang.Hariani, Dessy. 2011. Pengaruh Penerapan Good Corporate Governance terhadap Resiko Kreditdan Yield Sukuk Ijarah Korporasi. Tesis. Universitas Indonesia.Ifham, Ahmad. 2010. Buku Pintar Ekonomi Syariah. PT. Gramedia Pustaka Utama. Jakarta.Iswandi. 2012. Analisis Potensi Kebangkrutan PT. Berlian Laju Tanker, Tbk. Dengan Mengunakan Altman’s Z Score. Jurnal Business, Vol 3(2).Jamaldeen, Faleel. 2012. Islamic Finance For Dummies. Canada: John Wiley and Sons, IncJama’an. 2008. “Teori Manajemen Keuangan Pemasaran, Perbankan dan SDM, 2008, http://ekonomi.kabo.biz/2011/07/teori-sinyal.html. Jumingan. 2006. “Analisis Laporan Keuangan”. Bumi Aksara. Jakarta.Kamstra, Mark, et al. 2001.Combining Bond Rating Forecasts Using Logit.The Financial Review.Vol.(37): 75-96.Kementrian Keuangan Replubik Indonesia. 2012.Laporan Hubungan Dedikasi Investor 2012. (Sumber: http://www.kemkeu.go.id, diakses pada tanggal 30 Agustus 2016).Maria, Delli. 2014. Pengaruh Mekanisme Corporate Governance dan Profitabilitas Perusahaan terhadap Peringkat Obligasi. Jurnal Ilmiah ESAI, Vol 8(2).Manurung, A. H (2007). Pengelolaan Portofolio Obligasi. Elex Media Komputindo. Jakarta.Nafik, Muhammad. 2009. Bursa Efek Indonesia dan Investasi Syariah. PT. Serambi Ilmu Semesta Jakarta. Otoritas Jasa Keuangan. 2016. Statistik Pasar Modal Syariah. Direktorat Pasar Modal Syariah.Pemeringkat Efek Indonesia. 2016. Rating Methodology PEFINDO. (Sumber: http://www.pefindo.com, diakses pada tanggal 30 Agustus 2016).Pertiwi, Dian Ayu. 2014. Analisis Faktor-faktor yang Mempengaruhi Credit Rating dan Penurunan Credit Rating. Semarang.Pottier, Steven W. And David W Sommer. 1997. Agency Theory and Life Insurer Ownership Structure. The Journal of Risk and Insurance. Vol. 64. No. 3.Purwaningsih, Septi. 2013. Faktor yang Mempengaruhi Rating Sukuk yang DitinjaudariFaktorAkuntansidan Non Akuntansi.Accounting Analysis Journal, Vol.2(3).Putri, Grace. 2010. Analisis Faktor Akuntansi dan Non Akuntansi dalam Memprediksi Peringkat Obligasi Perusahaan Manufaktur. Jurnal Ilmu Administrasi dan Organisasi, Vol.17 (1): 70-78Quraish, M Shihab. 2002. Tafsir Al Mishbah. Vol 4. Hal 510. Penerbit Lentera Hati.Raharja & Sari. 2008. Perbandingan Alat Analisis (Diskriminan & Regresi Logistik) terhadap Peringkat Obligasi (PT Pefindo). Jurnal Bisnis dan Ekonomi. Vol. 4. No. 1. Rosyid, Rosmita&Evina. 2013. Analisis Pengaruh Mekanisme Good Corporate Governance dan Profitabilitas Perusahaan terhadap Peringkat Obligasi.Jurnal Akuntansi UKRIDA,Vol (1).Saputro, Galih. 2016. Analisis Corporate Governance, Faktor Akuntansi dan Non Akuntansi yang Mempengaruhi Rating Sukuk. Naskah Publikasi. Universitas Muhammadyah Surakarta.Sartono, Agus. 1996. Manajemen Keuangan Teori dan Aplikasi. Edisi Ketiga. Penerbit BPFE. Yogyakarta.Shihab, M. Quraish. 2002. Tafsir Al Misbah. Lentera Hati. Vol 4.Sucipto. 2003. Penilaian Kinerja Keuangan. Universitas Sumatra Utara.Syed, Salman. 2008. Islamic Capital Markets.Saudi Arabia:Islamic Research and Training Institute, IDB.